2018
DOI: 10.1177/0960327118781927
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hypothyroidism on testicular mitochondrial oxidative stress by activating the p38 mitogen-activated protein kinase and c-Jun NH2-terminal kinase signaling pathways in rats

Abstract: Thyroid hormone deficiency can impair testicular function. However, knowledge of the effects of mitogen-activated protein kinase (MAPK) pathways on testicular mitochondrial oxidative damage induced by hypothyroidism is still rudimentary. This study aims to explore the possible mechanisms of testicular mitochondrial oxidative damage in hypothyroidism rats. Wistar male rats were randomly divided into control (C), low- (L), and high-hypothyroidism (H) groups (1 ml/100 g body weights (BWs)/day 0, 0.001% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
3
2
0
Order By: Relevance
“…As for hormone receptors and membrane transporters, hypothyroidism increased Ar expression in the testes. Similar to the present study, Chang et al 49 observed an increase in testicular Ar mRNA in hypothyroid rats but a reduction in the AR protein levels. This suggests that there are post-transcriptional alterations in testicular AR expression in hypothyroid rats 49 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As for hormone receptors and membrane transporters, hypothyroidism increased Ar expression in the testes. Similar to the present study, Chang et al 49 observed an increase in testicular Ar mRNA in hypothyroid rats but a reduction in the AR protein levels. This suggests that there are post-transcriptional alterations in testicular AR expression in hypothyroid rats 49 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the present study, Chang et al 49 observed an increase in testicular Ar mRNA in hypothyroid rats but a reduction in the AR protein levels. This suggests that there are post-transcriptional alterations in testicular AR expression in hypothyroid rats 49 . Furthermore, the increase in Ar mRNA observed in hypo rats may be the result of the reduction in plasma testosterone, because androgens negatively regulat e Ar gene expression 50 , 51 .…”
Section: Discussionsupporting
confidence: 91%
“…These resulting in steroidogenesis inhibition in Leydig cells whereby TNF-α lessened testicular 3band 17b-17ß-hydroxysteroid dehydrogenase activity resulting in reduced testosterone level (Hales 2002;Hong et al 2004). Consequently, AR damage are occurred in response to testicular oxidative burden (Chang et al 2019;Yao et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, testicular cells are equipped with the transporters and enzymes required to maintain thyroid hormone homeostasis within the testes (Gao et al, 2014). Physiologically, TH is an important factor in redox balance, and alteration in thyroid homeostasis can lead to oxidative stress, apoptosis, and proton pump dysfunction (Chang et al, 2019). Hypothyroidism has been shown to disrupt proton pump (such as Ca2+-ATPase) activities, which in turn disrupts calcium homeostasis (Chang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, TH is an important factor in redox balance, and alteration in thyroid homeostasis can lead to oxidative stress, apoptosis, and proton pump dysfunction (Chang et al, 2019). Hypothyroidism has been shown to disrupt proton pump (such as Ca2+-ATPase) activities, which in turn disrupts calcium homeostasis (Chang et al, 2019). Maintaining intracellular calcium is important for mitochondrial function since calcium imbalance is a major trigger for mitochondrial dysfunction associated with oxidative stress and apoptosis (Nazıroğlu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%